2007
DOI: 10.1248/bpb.30.1648
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties of Three Isoforms of Trypsin Isolated from the Pyloric Caeca of Chum Salmon (Oncorhynchus keta)

Abstract: Trypsin, an important enzymes belonging to the large and diverse family of serine proteases, has been found in numerous higher mammals, fish, plants, insects and bacteria. Several studies on the isolation and characterization of trypsins from cold-adapted fishes, such as Atlantic salmon (Salmo salar), 1,2) chum salmon (Oncorhynchus keta), [3][4][5] Atlantic cod (Gadus morhua), 6) Greenland cod (Gadus ogac), 7,8) Antarctic fish (Paraotohhthenia magellanica), 9) Japanese anchovy (Engraulis japonicus), 10) and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This may be the most significant factor in the higher catalytic efficiencies of CST-1 and CST-2 compared with CST-3. The catalytic efficiencies (K m /k cat ) of the chum salmon trypsin isoforms (CST-1, CST-2 and CST-3) in this study during BAPA hydrolysis were 20-fold more efficient than that of bovine trypsin (BT) at 308 K and their enzyme activity increased more at low temperatures (298-278 K;Toyota et al, 2007). The catalytic efficiency of anionic Atlantic salmon trypsin (AST) is also about 20-fold higher than BT at 310 K and 35-fold higher at 277 K (Quzen et al, 1996).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This may be the most significant factor in the higher catalytic efficiencies of CST-1 and CST-2 compared with CST-3. The catalytic efficiencies (K m /k cat ) of the chum salmon trypsin isoforms (CST-1, CST-2 and CST-3) in this study during BAPA hydrolysis were 20-fold more efficient than that of bovine trypsin (BT) at 308 K and their enzyme activity increased more at low temperatures (298-278 K;Toyota et al, 2007). The catalytic efficiency of anionic Atlantic salmon trypsin (AST) is also about 20-fold higher than BT at 310 K and 35-fold higher at 277 K (Quzen et al, 1996).…”
Section: Discussionmentioning
confidence: 59%
“…In our previous paper (Toyota et al, 2007), the K m values of CST-1 and CST-2 during BAPA hydrolysis were found to be slightly higher than that of CST-3, which is the main isoform. The k cat values for CST-1 and CST-2 were about twice as high as that of CST-3.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…These appendages are present in only 60% of known fish species (Hossain and Dutta, 1996) and they differ in number, form, disposition and communication with the intestine (Khanna, 1961; Mohsin, 1962). The function of the pyloric caeca is to increase the surface area of the intestine (Buddington and Diamone, 1986) Pyloric caeca are involved in sugar, amino acid, peptide and lipid digestion and absorption (Buddington and Diamone, 1986; Horn, 1989; Lindsay and Harris, 1980; Martin andand Sandercock, 1967; Sastry, 1974; Toyota et al, 2007). Additionally, a secretory function of this organ and a role in salt and water balance (osmotic balance) have been postulated (Abaurrea‐Equisoah and Ostos‐Garrido, 1986; Anderson, 1986; Veillette et al, 2005).…”
Section: Introductionmentioning
confidence: 99%